Plant analysis as a method of diagnosing fertilizer requirements of citrus, with special reference to the Valencia variety - Bathurst, A. C (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc. in Agric.) -- University of Stellenbosch, 1948.